Relationship between vascular age and atherosclerosis-related cardiovascular diseases - R. N. Najafov (Российский кардиологический журнал, 2021)
Aim. To determine the relationship between vascular age (VA) and atherosclerosis-related cardiovascular diseases in patients with hypertension and hyperlipidemia.Material and methods. The study involved 241 residents of Baku. The mean age was 58,7±10,9 years. There were 119 women (49,4%) and 122 (50,6%) men. The mean body mass index was 27,77±4,19 kg/m2. Data on family history, smoking, obesity, diabetes, chronic kidney disease, revascularization, peripheral arterial disease, angina pectoris, drug intake, lipid profile, systolic and diastolic blood pressure were analyzed. Patient VA was estimated using an online calculator.Results. The patient VA was on average 78,0±15,1 years. Pearson's correlation analysis showed a positive correlation between biological age (BA) and estimated VA (0,719; 95% confidence interval: 0,651-0,775; p<0,001). Pearson's chi-squared test with Monte Carlo simulation showed that within 10-month followup, myocardial infarction (MI) in presented sample was more common in age subgroups of 50-59 (10,0%) and 60-69 (8,3%) years. At the same time, in the group defined by VA, myocardial infarction was more common in the age subgroup of 70-79 (7,0%) and >80 years (13,3%). MI+stroke+revascularization in the group defined by BA was more common in age subgroups of 50-59 (12,0%) and 60-69 (14,5%) years, and in the group defined by VA, MI+stroke+revascularization was more common in age subgroups of 70-79 (11,6%) and >80 years (19,9%).Conclusion. A significant positive correlation was found between BA and VA. In case of VA >70 years, the incidence of MI+stroke+revascularization increases approximately 3-5 times. Thus, the assessment of VA is an effective clinical tool that allows to inform the patient about possible cardiovascular events and to develop preventive measures.